(untitled) (Namibian Journal of Linguistics, Literature and Communication Studies, 2023)
The goal of this qualitative study is to investigate Namibian users’ language practices in social discourses on Namibian social media platforms. A hybrid linguistic environment is created when users using multiple languages online. However, there appear to be no studies that look at the language practices of users on Namibian social platforms online. The sample consisted of Facebook comments from users in responses to articles on the Fishrot case published in 2019. The first five posts published in each of the selected Namibian media were chosen, and comments in which users directly responded to each other’s were studied using internet ethnography, which tracks discourses across multiple online user comments. Discourse analysis was used as a method to analyse the data. Other sources on languages and multilingualism in Namibia were also used to inform the data. The data was organised under emerging themes that were informed by the central ideas in metrolingualism theory. According to the study, the language of socialization in Namibia remains primarily English; multilingualism is reflected in social online discussion but is limited to a few majority indigenous languages, Oshiwambo and Afrikaans.